PERENCANAAN JALUR EVAKUASI ERUPSI GUNUNG MARAPI KECAMATAN CANDUANG KABUPATEN AGAM - Rina Fitri Ani; Triyatno Triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to: 1) Determine the evacuation route for Mount Marapi in Canduang District, Agam Regency, 2) Determine the potential evacuation sites available on the Mount Marapi evacuation route in Canduang District, Agam Regency, 3) Calculate the capacity of evacuation sites on the Mount Marapi evacuation route in the District. Canduang, Agam Regency. This type of research uses quantitative methods, while the analysis technique is the Closest Facility Analyst on the Network Analyst, the Closest Facility Analyst is an extension used to find the closest evacuation site, the potential evacuation site is analyzed using the kingma formula seen from the evacuation site close to the road. In the main, evacuation sites are close to health facilities and complete facilities, while the capacity for evacuation sites is based on the 2008 National Disaster Management Agency Regulation. The results of the study are 1) Canduang District there are 105 evacuation routes to 41 evacuation points, evacuation routes are considered from seven variables, namely the Mount Marapi Disaster Prone Area (KRB), road length, road width, road materials / road pavers, road conditions, absence of bridges and directions. 2) All Evacuation Places in Canduang District have high potential to be used as temporary evacuation sites with a score of 11 – 13. 3) The capacity of evacuation sites is 10,629 people / person or 46% of the total population of 22,533 people / person. Based on the results of the research, the evacuation route and the potential of the evacuation site are optimal, while the capacity of the evacuation site is not optimal so that additional evacuation sites are needed. Keywords:Evacuation route, Potential evacuation site, Capacity.